Akulturasi Gamelan-Hadroh dalam Dakwah Kultural: Pendampingan Karakter dan Musikalitas Santri di Pondok Pesantren Darul Wangi Bedilan Ogan Komering Ulu Timur - Suyitno Suyitno; Ahmadi Ahmadi (Jurnal Pengabdian Kepada Masyarakat, 2026)
The utilization of traditional musical instruments in Islamic boarding schools (pesantren) often faces challenges such as limited instructors, stagnation in innovation, and poor rhythmic tempo stability in students' musical performance. This community service program aims to optimize the function of gamelan instruments through a clinical mentoring method acculturated with Islamic percussion instruments (hadroh) as a medium for cultural dawah. The partner for this program is the Darul Wangi Islamic Boarding School, Bedilan, East Ogan Komering Ulu. The implementation method was based on a participatory approach that included physical observation, collaborative arrangement formulation, and focused training using the isolated group practicing technique to separate the focus of male and female students based on group gender comfort. The psychomotor evaluation results showed a 100% success rate, with the students successfully mastering four collaborative sholawat arrangements with smooth tempo transitions. Affectively, this program successfully internalized core character values of discipline, reduction of sectoral ego in teamwork, and boosted students' self-confidence through an evaluation staging performance. Furthermore, this cross-cultural integration provides a tactical contribution to strengthening religious moderation and providing an emotional catharsis space for students. The program sustainability strategy has also been institutionalized through the establishment of an independent musical group management to ensure the continuity of inclusive cultural dawah in the modern era.